Vampire god : the allure of the undead in Western culture - Hallab, Mary Y., 1940- (Albany : SUNY Press, 2009)
"In [book title], [author] examines the mythic figure of the vampire from its origins in early Greek and Slavic folklore, its transformation by Romantics like Byron, Le Fanu, and Stoker, and its diverse representations in present-day popular culture. The allure of the vampire, [author] argues, lies in its persistent undeadness, its refusal to accept its mortal destiny of death and decay. Vampires appeal to our fear of dying and our hope for immortality, and as a focus for our doubts and speculations, vampire literature offers answers to many of our most urgent questions about the meaning of death, the nature of the human soul, and its possible survival after bodily dissolution."--Back cover
Vampires and science -- Vampires and society -- Vampires and psychology: body, soul, and self -- The religious vampire: reason, romantics, and Victorians -- The religious vampire: the twentieth century -- The vampire god: nature and the numinous.
Includes bibliographical references (pages 145-160) and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Vampires in literature; Vampire films; Vampires on television; Folk literature -- History and criticism; Fantasy fiction -- History and criticism; Vampires dans la littérature.; Vampires à la télévision.; Littérature populaire -- Histoire et critique; TRAVEL -- Special Interest -- Literary; LITERARY CRITICISM -- General; Fantasy fiction; Folk literature; Vampire films; Vampires in literature; Vampires on television; Fernsehsendung; Vampir; Literatur; Film; Bellettrie; Films; Vampiers; Religieuze aspecten; Vampir; culture -- Occident -- vampire -- Antiquité -- 21e s. (début); culture populaire -- vampire -- 20e s. (fin) -- 21e s. (début); LITERARY CRITICISM / General; Vampire films; Criticism, interpretation, etc; Vampire films; Films de vampires